RETRACTED: The effectiveness of the use of the drug “Furinaid” in complex therapy in the treatment of idiopathic cystitis in small pets - Alekseeva Tatyana; Krotova Olga; Savenkov Konstantin; Ubushaeva Dayana; Nimeeva Anna; Chuev Hongr (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001